(untitled) (Journal of Advances and Scholarly Researches in Allied Education, 2012)
IShall Not Hear the Nightingale islocated in the ambiguous and disturbed pre-partition period, and concentrateson the inner tensions and external movements of a well-to-do Sikh family in thePunjab from April 1942 to April 1943. It was the period of the ‘Quit India’conflagration, and naturally the relations between the bureaucracy and thepeople were more than strained.